Burden analysis of diabetic nephropathy caused by excessive intake of sugar-sweetened beverages in high and low SDI regions - Xue Wang; Guangyan Cai; Qing Ouyang; Xiangmei Chen (Frontiers in Public Health, 2025)
ObjectiveThe Global Burden of Disease Study (GBD) 2019 reveals an increasing prevalence of diabetic nephropathy caused by excessive intake of sugar-sweetened beverages in high and low SDI regions from 1990 to 2021.MethodsThis study comprehensively analyzed the burden of DN caused by SSBs in high and low SDI regions from 1990 to 2021 and projected the trends until 2040 using ARIMA models.ResultsThe results revealed distinct patterns and trends in age-standardized rates of deaths, DALYs, YLDs, and YLLs between the two regions. In high SDI regions, the age-standardized rates of deaths, DALYs, YLDs, and YLLs exhibited a consistent upward trend from 1990 (0.044, 1.425, 0.537, 0.888 per 100,000) to 2021 (0.096, 2.284, 0.67, 2.154 per 100,000). Projections for the age-standardized rates in high SDI regions from 2021 to 2040 indicate that these upward trends will persist, with deaths, DALYs, YLDs, and YLLs further increasing to 0.127, 3.629, 1.070, and 2.861 per 100,000. Conversely, low SDI regions displayed different trends. Although the age-standardized rates of deaths, DALYs, YLDs, and YLLs also increased from 1990 (0.018, 0.488, 0.071, 0.417 per 100,000) to 2021 (0.020, 0.522, 0.081, 0.441 per 100,000), the rate of increase was relatively slower compared to high SDI regions. Projections for the age-standardized rates in low SDI regions from 2021 to 2040 suggest that these upward trends will continue, with deaths, DALYs, YLDs, and YLLs further increasing to 0.016, 0.498, 0.105, and 0.398 per 100,000.ConclusionThis study provides a comprehensive analysis of the burden of type 2 diabetes nephropathy caused by excessive intake of sugar-sweetened beverages in high and low SDI regions. The results revealed distinct patterns and trends in age-standardized rates of deaths, DALYs, YLDs, and YLLs between the two regions.